√(16 -x) +√(x-14) = x² -30x +227 ; * * *
ОДЗ: { 16 -x ≥0 ; x-14 ≥0 ⇒x ∈[14 ; 16]. * * * √(16 -x) +√(x-14) = (x-15)²+2 * * *
√(1 -(x - 15)) +√(1+(x -15)) = (x-15)²+2 ;
* * * замена t =x -15 * * *
√(1-t) +√(1+t) =t² +2 * * * -1 ≤ t ≤1 * * *
1- t +2√(1-t²) +1+t =t⁴ +4t² +4;
2√(1-t²) = t⁴ +4t² +2 ;
Левая часть уравнения 2√(1-t²) ≤2 , а правая часть t⁴ +4t² +2≥ 2 .
Значит уравнение может иметь решение ,если только 2√(1-t²) =2 и t⁴ +4t² +2 =2.
2√(1-t² =2⇒t=0 ; t =x -15 =0 ⇒x=15.
при t=0 ⇒ t⁴ +4t² +2 =2.
--------
* * * * * * *
√(16 -x) +√(x -14) = x² -30x +227 .
f(x) =√(16 -x) +√(x -14) , x ∈[14 ; 16].
f(14) =√2 ;
f(16) =√2 .
f'(x) = ( √(16 -x) +√(x-14) ) ' =(√(x-14 ) - √(16 -x) )/2(√(16 -x) +√(14 -x)) ;
f'(x) = 0⇒x =15 .
f(15) =2.
maxf(x) =2 , если x =15 .
min(x² -30x +227) =min(2 +(x -15)²) ≥ 2.